Parameter optimization design of reducer gears based on differential evolution algorithm - MA YuFeng; NING Xin; ZHENG YanLing; ZHAO BingHao (Jixie qiangdu)
According to Shanghai road driving cycle, a light-weight design model for gear in driving deceleration system with finite life is developed, in consideration of random continuous loading characteristics and low amplitude load strengthening effect on 20CrMnMo steel. Based on linear damage theory, developed load spectrum and continuous load spectrum with low amplitude load strengthening were implemented to calculate fatigue damage. To minimize gear volume, a light-weight optimization model was established with the constraint of fatigue damage, and differential evolution algorithm was then adopted to solve the model. Experimental results show that the designed model can find the optimal gear parameters quickly and accurately, and the best optimized parameters can be obtained when the continuous load spectrum is used and the low amplitude load strengthening effect is taken into consideration. The optimization model designed in this paper has excellent transferability and can be directly migrate to light-weight optimization of other transmission parts.